The Rights of Non-Muslims In the Malaysian Constitution and Its Comparison with The Sahifa Madinah - Muhammad Ikram bin Abu Hassan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Providing rights in a country is essential, especially for organizing Malaysian citizens which has a different religion. The Malaysian constitution is the reference for knowing this right for non-Muslims. And the biography of the Prophet the Prophet had stated in the Sahifah Al-Madinah that these rights are a reference for the Islamic nation. It is worth noting that we compare the two constitutions to find out what can be improved towards non-Muslims in the Malaysian constitution. The purpose of this study is to research the Malaysian constitution about the rights of non-Muslims and then compare it with what was reported in Al-Madina Sahifah to discover what could be improved in the Malaysian constitution. The method used in this study is the inductive approach based on extrapolation of historical documents with the aim of obtaining related data. Then the data is analyzed using an inferential method to generate general conclusions regarding the rights of non-Muslims in both constitutions. Among the most important findings of the study is that there is a great similarity between these two documents in providing rights for non-Muslims. Then non-Muslims in the Islamic state are considered citizens with Muslims. It is permissible to cooperate with non-Muslims to defend the state to provide security and safety. Every Muslim and non-Muslim citizen has the right and duties in the Islamic state.